Brain ultrasound for diagnosis and prognosis in the neurological intensive care unit: a mini review for current development. (3rd August 2019) - Zhu, Haomeng; Geng, Xiaokun; Rajah, Gary B.; Fu, Paul; Du, Huishan
ABSTRACT: Objective: Transcranial doppler ultrasonography (TCD) is one of the few tools in the Neurological Intensive Care Unit (NICU) that allows for real-time monitoring of cerebral blood flow while also being non-invasive. This review examines the current use of TCD monitoring in the NICU. Method: We completed a literature review using Google Scholar and Pubmed. Relevant articles were included in this review. Results: The role of TCD in the NICU continues to evolve since its infancy in the 1980s. TCD use is now standard of care of for some neurological maladies. The significant advantages of TCD include convenience of use, non-invasive nature, bedside operation, high accuracy, and absence of interference from external factors such as temperature and sedatives. Conclusion: This review examines the current use of TCD monitoring in the NICU. Through review and continued development of similar non invasive technologies NICU care continues to innovate and evolve. Abbreviation: TCD: Transcranial Doppler